Holding space and engaging with difference: Navigating the personal theories we carry into our pedagogical partnership practices - Ostrowdun, Christopher; Friendly, Rayna; Matthews, Kelly; de Bie, Alise; Roelofs, Frits (International Journal for Students as Partners, 2020)
Partnerships between students and faculty are increasingly established within higher education. Everyone’s unique life story or background influences how they understand partnership praxis. Acknowledging individual understandings of student-faculty partnership matters because personal stories can influence how such partnerships form, function, and evolve. We, as students and faculty, share our individual theories of partnership to illuminate differing ways people can make sense of partnership as praxis. Using a reflective, autoethnographic research approach, we unpack two interdependent threads from our narratives: (a) holding space for how personal histories shape the experience of partnership and (b) engaging the messiness of partnership. To understand and nurture inclusive practices, we contend, means engaging the unique standpoints and social positions that both students and faculty bring into partnerships. Instead of attempting to collapse and converge different perspectives of partnership, we take pause to consider how these differences can enrich partnerships and be honoured throughout a partnership